2011
DOI: 10.2298/mpns1102029g
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor in melanocytic nevi

Abstract: Melanocytic nevi represent a benign neoplastic proliferation of melanocytes. The level of vascular endothelial growth factor expression in these proliferations is low in most cases; whereas an increased expression of this factor may be an indicator of pre-neoplastic changes in melanocyte lesions. We performed a semi-quantitative assessment of the level of vascular endothelial growth factor expression (score 0 to 3) on samples taken from 34 patients with benign melanocyte alterations of the skin. Melanocytic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…[10][11][12] Previously, some reports revealed that melanocytic nevus had no or low expression of VEGF. 13,14 As for FGF-2, Giehl et al 15 reported that 55% cases of melanocytic nevus expressed FGF-2, and the staining intensities were moderate except for one case with strong staining. However, in our case of ASN, these angiogenic factors were strongly expressed in the melanocytes as well as in the endothelial cells, and the staining intensities in the immunohistochemical studies were higher than in our previously experienced cases of melanocytic nevus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Previously, some reports revealed that melanocytic nevus had no or low expression of VEGF. 13,14 As for FGF-2, Giehl et al 15 reported that 55% cases of melanocytic nevus expressed FGF-2, and the staining intensities were moderate except for one case with strong staining. However, in our case of ASN, these angiogenic factors were strongly expressed in the melanocytes as well as in the endothelial cells, and the staining intensities in the immunohistochemical studies were higher than in our previously experienced cases of melanocytic nevus.…”
Section: Discussionmentioning
confidence: 99%
“…In PG, VEGF and FGF‐2 have been shown to play vital roles in its angiogenesis, which could be produced mainly by endothelial cells and inflammatory cells . Previously, some reports revealed that melanocytic nevus had no or low expression of VEGF . As for FGF‐2, Giehl et al.…”
Section: Discussionmentioning
confidence: 99%